Optimization of small agricultural producer’s taxation by creating innovative-integrated structures - Kononenko, Lesia; Кононенко, Леся Віталіївна; Atamas, Olexander; Атамас, Олександр Петрович; Nazarova, Halyna; Назарова, Галина Борисівна; Selishcheva, Yelyzaveta; Селіщева, Єлизавета Володимирівна; Kononenko, Serhii; Кононенко, Сергій Олексійович (Поліський національний університет, 2022)
Issues of tax optimisation of business entities have always been in the centre of attention of taxpayers. Solving this issue requires strong human, technical, and other types of support. There are substantial features of the functioning of small-scale agricultural producers, which make it difficult to optimise their taxation. Presently, it is possible to solve this issue by creating innovative and integrated structures. The purpose of this study was to substantiate the feasibility of creating innovative and integrated structures in the agro-industrial complex, which should lead to optimisation of taxation of Ukrainian small-scale agricultural producers. Both general scientific and special research methods were used in the preparation of this study, namely: logical generalisation – for theoretical justification of the need to create innovative and integrated structures to optimise the functioning of small scale agricultural producers; mathematical and system analysis – to justify the feasibility of creating integrated structures to optimise the taxation of small scale agricultural producers, etc. The study of the theoretical foundations and practices of taxation of Ukrainian small-scale agricultural producers allowed substantiating the feasibility of creating innovative and integrated structures in the agricultural sector of the economy. It was found that in the structure of agricultural enterprises, the largest share belongs to small enterprises that, according to the specifics of their activities, are geographically remote from the centres of civilisation (labour market, tax services, internet resources, etc.) and do not have the opportunity to have highly qualified employees in their staff. It was proved that it is possible to optimise the taxation of small-scale agricultural producers by creating innovative and integrated structures. It is proposed to create integration structures by involving small-scale agricultural producers and employees of advisory services in accounting and analytical work. Delegating complex and variable tasks to a highly qualified specialist would substantially optimise the tax policy of an agricultural enterprise. Further research should be carried out towards developing a mechanism for optimising the functioning of agricultural producers in the context of the development of digital technologies. Питання оптимізації оподаткування суб’єктів господарювання завжди знаходились у центрі уваги платників податків. Вирішення цього питання потребує потужного кадрового, технічного та інших видів забезпечення. Існують суттєві особливості функціонування дрібнотоварних сільськогосподарських виробників, які зумовлюють складність оптимізації їх оподаткування. Вирішити це питання на сьогодні можливо шляхом створення інноваційно-інтегрованих структур. Метою проведеного дослідження є обґрунтування доцільності створення інноваційно-інтегрованих структур у агропромисловому комплексі, що повинно привести до оптимізації оподаткування українських дрібнотоварних сільськогосподарських виробників. При підготовці статті було використано як загальнонаукові так і спеціальні методи дослідження, а саме: логічного узагальнення – для теоретичного обґрунтування необхідності створення інноваційно – інтегрованих структур з метою оптимізації функціонування дрібнотоварних сільськогосподарських виробників; математичні та системного аналізу – для обґрунтування доцільності створення інтегрованих структур з метою оптимізації оподаткування дрібнотоварних сільськогосподарських виробників тощо. Дослідження теоретичних засад та практичного досвіду оподаткування українських дрібнотоварних сільськогосподарських виробників дало змогу обґрунтувати доцільність створення інноваційно-інтегрованих структур в аграрному секторі економіки. Визначено, що у структурі сільськогосподарських підприємств найбільша питома вага належить малим підприємствам, які за специфікою своєї діяльності територіально віддалені від центрів цивілізації (ринку праці, податкових служб, інтернет-ресурсів тощо) та не мають можливості мати у своєму штаті висококваліфікованих працівників. Обґрунтовано, що оптимізувати оподаткування дрібнотоварних сільськогосподарських виробників можливо шляхом створення інноваційноінтегрованих структур. Запропоновано створення інтеграційних структур шляхом залучення до обліково-аналітичної роботи дрібнотоварних сільськогосподарських виробників, працівників Дорадчих служб. Делегування складних і варіативних завдань висококваліфікованому спеціалісту дозволить суттєво оптимізувати податкову політику сільськогосподарського підприємства. Подальші дослідження доцільно проводити у напряму розробки механізму оптимізації функціонування сільськогосподарських товаровиробників в умовах розвитку digital-технологій.
Оптимізація оподаткування дрібнотоварного сільськогосподарського виробника шляхом створення інноваційно-інтегрованих структур
Keywords: consulting; консультування; digital technologies; digital-технології; agricultural advisory services; сільськогосподарські дорадчі служби; agro-industrial complex; агропромисловий комплекс